2012
DOI: 10.1136/thoraxjnl-2011-200949
|View full text |Cite
|
Sign up to set email alerts
|

Systemic elastin degradation in chronic obstructive pulmonary disease

Abstract: Background Development of emphysema and vascular stiffness in chronic obstructive pulmonary disease (COPD) may be due to a common mechanism of susceptibility to pulmonary and systemic elastin degradation. Objectives To investigate whether patients with COPD have evidence of systemic elastin degradation in the skin. Methods The authors measured cutaneous elastin degradation using immunohistochemistry (percentage area of elastin fibres) in sun-exposed (exposed) and nonsun-exposed (non-exposed) skin biopsies in 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(78 citation statements)
references
References 53 publications
4
69
0
5
Order By: Relevance
“…(74% w wieku ≥ 65 lat), określono częstość występowania chorób sercowo-naczyniowych, która była znamiennie wyższa u tych pacjentów w porównaniu z grupą kontrolną bez POChP. Wśród patologii sercowo-naczyniowych najczę-ściej stwierdzono zatorowość płucną 5,46 [12]. W innym badaniu zauważono, że chorzy na POChP mają ponad dwukrotnie wyższe ryzyko względne wystąpienia zawału serca w ciągu pierwszych 5 dni i 1,26 raza wyższe ryzyko udaru mózgu w czasie 49 dni od epizodu zaostrzenia choroby obturacyjnej [13].…”
Section: Choroby Sercowo-naczyniowe a Pochpunclassified
See 1 more Smart Citation
“…(74% w wieku ≥ 65 lat), określono częstość występowania chorób sercowo-naczyniowych, która była znamiennie wyższa u tych pacjentów w porównaniu z grupą kontrolną bez POChP. Wśród patologii sercowo-naczyniowych najczę-ściej stwierdzono zatorowość płucną 5,46 [12]. W innym badaniu zauważono, że chorzy na POChP mają ponad dwukrotnie wyższe ryzyko względne wystąpienia zawału serca w ciągu pierwszych 5 dni i 1,26 raza wyższe ryzyko udaru mózgu w czasie 49 dni od epizodu zaostrzenia choroby obturacyjnej [13].…”
Section: Choroby Sercowo-naczyniowe a Pochpunclassified
“…Związek między nadciśnieniem tętniczym a POChP może być wyjaśniany niszczeniem włókien elastycznych i zwiększeniem odkła-dania się włókiem kolagenowych, co prowadzi do usztywnienia tętnic, które jak zostało wykazane w badaniach, jest bardziej nasilone w POChP i było związane z obniżeniem wartości FEV 1 i nasileniem rozedmy [45]. Wyniki ostatnich badań wskazują na możliwy związek zwiększonej sztywności naczyniowej z intensywniejszą utratą elastycznej tkanki łącznej, co ma miejsce również w układzie oddechowym i powoduje zmiany rozedmowe [46]. Powstawaniu powikłań sercowo-naczyniowych może także sprzyjać aktywacja układu współczul-nego obserwowana u chorych na POChP [47].…”
Section: Patogeneza Współistnienia Pochp I Chorób Sercowo-naczyniowychunclassified
“…10,27,39,45 In chronic obstructive lung diseases, Maclay et al demonstrated that systemic elastin degradation, combined with the upregulation of MMP-2 and MMP-9, is associated with chronic obstructive lung diseases. 17 Though human LF cells are composed of various cell types, cells from healthy LF are known to have fibroblast-like features, and human fibroblasts secrete MMP-2 and MMP-9.…”
Section: Discussionmentioning
confidence: 99%
“…COPD involves an intricate array of cellular, functional, and organ-related events that result in airflow limitation by virtue of a prolonged time constant of lung emptying (Garcia-Aymerich et al, 2011;Maclay et al, 2012). COPD is a chronic condition that affects approximately three million worldwide and current disease estimates show that COPD will be the third leading cause of death by 2020 (Singh et al, 2011;Vestbo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%